Proceedings of the International Conference and Young Researchers' Forum: 'Natural resource use in Central Asia: institutional challenges and the contribution of capacity building'. Held in Giessen, 1st October 2013 - Mirza Nomman Ahmed; Ira Pawlowski (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2013)
[LIST OF CONTENT] SH. KENJABAEV, I. FORKUTSA, M. BACH, H.G. FREDE: Performance evaluation of the BUDGET model in simulating cotton and wheat yield and soil moisture in Fergana valley ... 1 / KANAYIM TESHEBAEVA, HENRIETTE SUDHAUS, H.-U. WETZEL, SIGRID ROESSNER, HELMUT ECHTLER AND ALEXANDER ZUBOVICH: Radar remote sensing for surveying and monitoring of earthquakes and mass movements in Southern Kyrgyzstan ... 15 / DAVRON ABSALYAMOV: Efficiency of wheat and cotton producing farms in Uzbekistan: a Stochastic Frontier Approach ... 23 / ILKHOMJON ASLANOV: Dust storms, dust transfer and depositions in the southern Aral Sea region ... 27 / M. BEKCHANOV, A. BHADURI, C. RINGLER: Is Rogun a Silver Bullet for Water Scarcity in Central Asia? ... 33 / M. DUISHONAKUNOV, S. IMBERY, L. KING: Assessing the recent Glacier retreat in Chon and Kichi Naryn Catchments, Kyrgyz Republic ... 37 / I. RADCHENKO, I. FORKUTSA, L. BREUER AND H.-G. FREDE: Hydrological modelling in arid catchments with data scarcity (Ferghana Valley, Central Asia) ... 43 / NATALYA TSYCHUYEVA, ANNETTE OTTE, LEV SPIVAK: The Analysis of Land Cover Changes in Mountain Region using Remote Sensing Data ... 45 / G. UMIRZAKOV, F. BARTHOLD, K. SCHNEIDER, I. FORKUTSA., L. BREUER, G. STULINA, V. DUKHOVNY, H.-G. FREDE: Estimation of phreatic evaporation in irrigation agriculture using stable isotopes ... 51 / FREDERIKE GEHRIGK, THOMAS HERZFELD, INSA THEESFELD: Farmers' perceptions of land and water property rights: Discrepancies between de jure and de facto rights in Tajikistan ... 63 / AHMAD HAMIDOV, MUKHAMADKHAN KHAMIDOV, ANDREAS THIEL: Institutional analysis of irrigation management in Uzbekistan using Qualitative Comparative Analysis: Case studies of water consumers associations in Bukhara region ... 67 / GULMIRA GAFAROVA, OLEKSANDR PEREKHOZHUK, THOMAS GLAUBEN: Pricing Behaviour of Kazakh, Russian and Ukrainian Exporters in the International Wheat Market ... 89 / PARVIZ KHAKIMOV: The impact of WTO accession growth on agricultural sector of Tajikistan ... 95 / ZUURA MAMADALIEVA: State of water and land use in south-western Kyrgyzstan ... 107 / LYAZZAT NUGUMANOVA: Analysis of Fossil Fuel Subsidies in Kazakhstan ... 109 / SALTANAT SABITOVA: Kazakh emissions trading scheme: legal implications for land use ...117 / DONIYOR SATTAROV, PURAN MAL: Impacts of Liberalization on Agriculture and Trade: A Case Study of Uzbekistan ... 121 / ELIZA ZHUNUSOVA: Policy-induced Distortions to Farmer Incentives and Their Impact on Agricultural Land Use in the Kyrgyz Republic ... 129 / UTKUR DJANIBEKOV, ASIA KHAMZINA, GRACE B. VILLAMOR, JOHN P.A. LAMERS: Economic analysis of afforestation of marginal croplands in Uzbekistan ... 137 / ANDREI DÖRRE: Legal Arrangements and Pasture-related Socio-ecological Challenges in Kyrgyzstan ... 149 / SHAKHZOD AVAZOV: Socio-economic Features of the Agro-pastoralists in the Zarafshan Valley, NW Tajikistan ... 155 / ALISHER ERGASHEV: How Fruit Consumption Might Be Fruitful for the Economy: Analyzing Effects of Improvements in Fruit and Vegetable Availability and Accessibility in Uzbekistan ... 171 / B.GOJENKO, I-U. LEONHAEUSER, G. STULINA: Land use, food and nutrition security - case study in rural Uzbekistan ... 185 / SHAVKAT HASANOV AND FARHOD AHROROV: Uzbekistan's Agriculture- Status Quo, Challenges and Policy Suggestions ... 189 / ISMAILOVA BASHORAT: The Aral Sea desiccation: Socio-economic effects in case of the Republic of Karakalpakstan, Uzbekistan ... 205 / ZHAMILIA SYDYGALIEVA: Causes and Impact of Migration on Economic Development of Kyrgyzstan ... 217 / ALIYA TONKOBAYEVA: Environmentally induced migration and displacement in Kazakhstan ... 227
Keywords: 330; natural resources; water; agriculture; climate change; Central Asia